On the improved adhesion of NiTi wires embedded in polyester and vinylester resins (Fracture and Structural Integrity, 2014)
This paper discusses the effect of different surface treatments on shape memory alloy wires embedded in PolyEster (PE) and VinylEster (VE) polymeric matrices. In particular, two types of chemical etching and a chemical bonding with a silane coupling agent have been performed on the surfaces of the wires. Pull-out tests have been carried out on samples made from a specifically designed Teflon mould. Considering the best results of the pull-out tests obtained with PE resin, the debonding induced by strain recovery of 4%, 5% and 6% pre-strained NiTi wires has been evaluated with the wires being subjected to different surface treatment conditions and then being embedded in the PE matrix. The results prove that the wires functionalised and embedded in the PE resin show the maximum pull-out forces and the highest interfacial adhesion. Finally, it has been found that debonding induced by strain recovery is strongly related to the propagation towards the radial direction of sharp cracks at the debonding region.
Keywords: Smart materials